(untitled) (Philosophy and Progress, 2024)
This paper focuses on Seyyed Hossein Nasr’s views of modern science. By focusing on Nasr’s opinion of modern science this paper explores how and why he rejects mechanical and positivist views of modern scholars. This research examines why he accepts the theory of creation and appreciates the spiritual and religious worldviews of science. In so doing, this article contributes to the ongoing discourse on the issue of modern science and eternal wisdom. By reviewing the relevant literary sources, some required data are collected and then used in the analysis hereafter. In this discussion Nasr talked about practicing science while keeping religious beliefs integrated. That is why, the existence of the creator of the world has been acknowledged. Whereas he excelled in the knowledge of science. As a result, the limitations of science arise in his mind. The philosophical problems he faced in his youth were not solved by modern science or western philosophy but were solved by the holy Qur’an. He accepts Tawheed or the oneness of God. Although he accepts modern science, he criticizes the resulting secularism. Nasr said that science should be practiced while maintaining religious values. His response to modern Science was to subordinate it to the systems and principles of the Islamic worldview. Moreover, to him, Modern Science was the largest framework of Knowledge (Ilm). This Modern science does not violate the core values of Islamic knowledge but inspires it with divine inspiration. In this case, the method came to be known as the Islamization of knowledge. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 215-240